O lugar do manicômio: relato da experiência de desconstrução de um hospital psiquiátrico no interior do Nordeste - Kinker, Fernando Sfair (2007)
This dissertation has as its object the transformation experience of a psychiatric hospital located in an inland city of the Brazilian Northeast. It gives an account of the Federal Government intervention performed by the Ministry of Health in that hospital that took place in 2005 and makes some reflections about the role of the mental institutions in the contemporary society. We argue that nowadays psychiatric hospitals do not operate based on a disciplinary logic, that supported the development of the asylums for many years, but under a new logic of abandoning, tuned with the new forms of deregulation that characterize the new standards of sociability of the present times. The theoretic framework has contributions from Franco Basaglia and collaborators, in the perspective of practical-theoretical deinstitutionalization, and from Michel Foucault s works on the psychiatric hospital genealogy and the relation between power and knowledge. Also there are, although fragmentary and punctual, references to many others authors and concepts within which we highlight the Edgar Morin s concept of Complexity, that warn us to not simplify neither the madness phenomenon, nor the responds given to it. The body of the work is compounded by a logbook, written by the time of the events, and reflections related to it. The stake here is that demonstrating this new logic of abandoning of the mental institutions, this account may contribute to the practice and theory of the current psychiatric reform in Brazil